Production patterns in the estuary of the Razdolnaya River in period of freezing - Vladimir I. Zvalinsky; Anna A. Mar’Yash; Pavel Ya. Tishchenko; Sergey G. Sagalaev; Petr P. Tishchenko; Maria G. Shvetsova; Ruslan V. Chichkin; Tatyana A. Mikhailik; Alexey M. Koltunov (Известия ТИНРО, 2016)
Light conditions and nutrients supply, as factors of primary production, are considered for the Razdolnaya River estuary in period of freezing (January-March). Water samples were collected at the water surface and at the bottom for measuring of salinity and concentrations of chlorophyll (Chl), phosphate, nitrite, nitrate, ammonium, and silicate. Profiles of water temperature, conductivity, Chl fluorescence, and turbidity were measured in situ by CTD-probe RBR XR-620; besides, vertical attenuation of PAR was measured at each station. The internal estuary (salinity < 10 ‰) was characterized by high values of the light diffuse attenuation coefficient ( kd ≈ 2 m-1 that corresponded to the euphotic depth zeu < 2.5 m) because of high turbidity (> 5 FTU) and high concentration of humine substances (up to 2 mgC/l) in the river waters. The ice cover lowered light intensity in the river water, too. In the zone close to the river bar with salinity 1-25 ‰, Chl concentration was 0.4-1.7 mg/m3 irrespective of salinity. DIN (dissolved inorganic nitrogen) and DISi (dissolved inorganic silicon) had conservative behaviour in this zone, the DISi : DIN ratio was ≈ 0.7-1.1.These features indicate an absence of significant production or destruction of organic matter in the internal estuary. However, intensive removal of dissolved inorganic phosphorus (DIP) (up to 80 %) was observed in this zone, that’s why the extraordinary high DIN : DIP ratio was observed under salinity 5-20 ‰ (up to 200 : 1, though the usual DIN : DIP ratio in the river water is close to Redfild ratio: DIN : DIP = (21-27) : 1). In the external estuary (salinity15-32 ‰), the water became more transparent ( kd = 0.5-0.3 m-1; zeu ≈ 9-15 m) and both chlorophyll concentration and dissolved oxygen content became higher (Chl up to 20 mg/m3, DO up to 500 mM/kg) as the result of high primary production, whereas nutrients concentrations became lower: DIP were completely removed and DIN and DISi retained 10-25 % of their initial values in the river water. The primary production value was evaluated by two ways: on the data of light intensity and on the data of nutrients removal. The light conditions in the internal estuary in February-March corresponded to the value 20-80 mgC/m2d which declines in 6-13 times and 50-100 times (close to zero) under the ice and under the ice with snow, respectively. In the external estuary, the light conditions in March corresponded to the value 300-600 mgC/m2d in the areas without ice and to the value lower in 6-13 times under the ice. The nutrients removal corresponded to the primary production value ≈ 200-400 mgC/m2d in the external estuary, irrespective of ice cover, that is close to the previous estimation by light conditions. So, the primary production in the Razdolnaya River estuary changes in winter in the range from 0 to 500 mgC/m2d, increasing seaward, the ice and snow are the factors of its limitation by light.